Sanctuary as a moving practice : The dynamics between diaconia, liturgy and politics during the Church Asylum in The Hague, 2018–2019 - Meijers, Erica (Stellenbosch Theological Journal, 2024)
In the winter of 2018–2019, a refugee family threatened with deportation from the Netherlands, found sanctuary in a church in The Hague. The police weren’t allowed to enter the building during a church service; this led to a period of three-month non-stop worshipping, causing vivid debates in both church and society. The sanctuary brought together the public presence of faith, often expressed in diaconal work, and the hidden, intimate spirituality that is associated with worshipping. Words usually spoken during Sunday services, and deeds frequently performed out of sight in diaconal practices, met during the sanctuary, brought together by political policy. This situation makes the sanctuary suitable to explore the dynamics between Diaconia, Liturgy and Politics, the three constitutional elements of the sanctuary in The Hague. The results are based on research in the archives of the sanctuary and empirical research during and after the sanctuary, interviewing both organizers and participants about their experience within this triangle. The article aims to find some answers to the question how diaconal theology contribute to a Church which is relevant in public life. First, the article describes the sanctuary as a diaconal practice in relation to its political context, it then turns to the role of Liturgy during the sanctuary, and finally it envisions the connection between Liturgy and Diaconia in the particular political context of the sanctuary.